Determinants and long‐term outcomes of largely uncovered struts in thin‐struts drug‐eluting stents assessed by optical coherence tomography. (20th January 2023) - Moretti, Francesco; Bernelli, Chiara; Pellegrini, Dario; Boccuzzi, Giacomo; Colombo, Francesco; Sirbu, Vasile; Vassileva, Angelina; Fiocca, Luigi; Canova, Paolo; Bezerra, Hiram; Pereira, Gabriel T. R.; Cereda, Alberto; et al.
Abstract: Background: Uncovered struts are a determinant of stent failure. The impact of plaque composition and procedural factors on the occurrence, evolution, and outcomes of uncovered struts in a high‐risk setting has not been investigated. Objective: To investigate the determinants and long‐term clinical impact of largely uncovered struts (LUS) in thin‐struts drug‐eluting stents (DES) implanted in complex lesions by intracoronary optical coherence tomography (OCT). Methods: Ninety patients with multivessel disease undergoing staged complete revascularization were randomly assigned to bioabsorbable or durable polymer DES. OCT were serially performed during the index procedure, at 3‐ and 18‐month follow‐up, and analyzed by an independent core lab. Struts were defined uncovered by OCT if no tissue was visible above the struts. LUS were defined as ≥30% of uncovered struts at 3‐month follow‐up. Clinical outcomes were the occurrence of target vessel failure (TVF) and major adverse cardiac and cerebrovascular events (MACCE) at 5‐year follow‐up. Results: LUS occurred in 31 patients (34.4%) regardless of stent platform. At 5 years, no differences were observed in the rate of TVF (12.7% vs. 13.4%; p = 0.91) and MACCE (23.9% vs. 24.9%; p = 0.88) between the two groups. At multivariate logistic regression, plaque rupture, mean lumen diameter, proximal reference vessel area, and maximum stent deployment pressure were independent predictors of LUS. Conclusions: LUS are a frequent finding in complex coronary lesions treated with thin‐struts DES, especially in the presence of plaque rupture. However, in this study, no significant safety signal related to LUS emerged in long‐term follow‐up.